2010
DOI: 10.4103/0970-1591.74434
|View full text |Cite
|
Sign up to set email alerts
|

Etiopathogenesis and management of bladder dysfunction in patients with posterior urethral valves

Abstract: Posterior urethral valves are the commonest cause of urethral obstruction in a male child. It has significant effects on the development of upper urinary tracts and in the evolution of urinary bladder function. The effect on the kidneys and the urinary bladder persists even after the successful management of the obstructing valves. A detailed evaluation of the associated bladder dysfunction will help in planning management protocols that will improve the long-term outcome of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 80 publications
0
29
0
1
Order By: Relevance
“…34 Filling and emptying of the bladder up until the third trimester lead to remodeling of the bladder wall. 35 Obstruction by PUVs impairs this process, contributing to long-term bladder dysfunction. 35…”
Section: Phases Of Kidney and Urinary Tract Developmentmentioning
confidence: 99%
“…34 Filling and emptying of the bladder up until the third trimester lead to remodeling of the bladder wall. 35 Obstruction by PUVs impairs this process, contributing to long-term bladder dysfunction. 35…”
Section: Phases Of Kidney and Urinary Tract Developmentmentioning
confidence: 99%
“…Posterior urethral valves (PUV) are the most common cause of congenital lower urinary tract outflow obstruction in male infants with an incidence of 1:5,000 male infants and 1:25,000 live births. [ 1 2 3 ] The incidence is unknown in our sub-region. Uba et al [ 1 ] in Jos, Nigeria reported 3–8 cases per annum.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, PUV are now commonly diagnosed by the postnatal evaluation of infants who had prenatal hydronephrosis. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…3 Due to the obstructive nature of PUV, development of detrusor hypertrophy, low bladder compliance, and high pressure are some of the subsequent changes that take place in the urinary bladder. 1,4 Such changes in the detrusor muscle must be considered in the context of any future surgical intervention, as they can greatly impact placement and drainage of urinary catheters. Casale forewarns that the use of a Foley catheter may cause irritation and subsequent bladder spasms in children with PUV.…”
Section: Discussionmentioning
confidence: 99%